THE IMPLEMENTATION OF BILLINGUAL LEARNING: A STUDY AT MUTIARA BUNDA INCLUSIVE SCHOOL IN CILEGON CITY - Sintawati, Fairus (IJOSMAS, 2021)
This research will describe about implementation of bilingual for learning. This research aims to describe of bilingual learning at inclusive elementary school students. The researcher will use a descriptive qualitative. Students At Mutiara Bunda Inclusive Elementary school provided equal opportunities for all children, regardless of their multifaceted differences, and where the system adapts to the needs of each child. Bilingual learning at Mutiara Bunda School takes the form of basic language learning such as learning vocabulary and basic conversations and is to taught to students gradually.